"THE IMAGE OF WANDERING" IN MODERN UZBEK PROSE IN THE INTERPRETATION OF ISAJON SULTAN'S WORK "THE ETERNAL WANDERER". (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article examines the image of wandering in the novel "The Eternal Wanderer" by Isajon Sultan.